Meeting the food security challenge for nine billion people in 2050: What impact on forests?. (May 2020) - Bahar, Nur H.A.; Lo, Michaela; Sanjaya, Made; Van Vianen, Josh; Alexander, Peter; Ickowitz, Amy; Sunderland, Terry
Highlights: Majority forecasts for feeding the future global population predict an increase in a croplands at the expense of forests and pastures. A third of the forecasts shows that it is feasible to halt further agricultural expansion and mitigate climate change. Policy that provides economic incentives for carbon stock conservation and enhancement is the only effective option to reverse the trend of forest loss.